(untitled) (Minerva, 2019)
The author explains the notions of past potentialis and irrealis. The optative may express past potentialis and irrealis in Homeric works, but normally do not in the classical period. There are, however, a few instances of that modal use of the optative in post-Homeric literature. The author shows, in the second part, by a comparative analysis of some of Homer’s, Euripides’ and Sophocles’ texts, how in the classical age these unusual modal constructions with the optative are even present in the works of Sophocles.